A simple method of obtaining pure microconidia in Neurospora crassa - A. Pandit; R. Maheshwari (Fungal Genetics Reports, 1993)
In order to examine the nuclear types that may be carried in strains of Neurospora collected from nature, we desired a method of selectively inducing microconidiation in mycelia whereby uninucleate microconidia could be obtained for isolating homokaryotic derivatives. We have devised a simple and highly effective method of obtaining pure microconidia from wild-collected strains as well as from N. crassa 74-OR23-1VA.